Differential achievements in childhood immunization across geographical regions of Pakistan: analysis of wealth-related inequality - Owais Raza; Fahad Saqib Lodhi; Esmaeil Khedmati Morasae; Reza Majdzadeh (BMC, 2018)
Abstract Background Childhood immunization is one of the most cost-effective interventions for child health. Still, many children are not able to receive completed immunization status. Wealth - related inequality in immunization is considered a major reason for equitable coverage of immunization in Pakistan. Therefore, we examine wealth-related inequality in completed childhood immunization and to assess achievement indices across geographical regions in Pakistan. Methods The analysis was based on a nationally representative demographic and health survey (DHS) of Pakistan, conducted in 2012-13. We examined completed childhood (12-23 months) immunization in the various regions of the country and we used concentration, extended concentration and achievement indices to demonstrate inequality across geographical regions in Pakistan. Results Inequality in completed childhood immunization was seen in Pakistan with concentration index (CI) of 0.181 (95% CI: 0.164-0.209). Regions with high average of complete immunization showed lower inequality except for Sindh. Despite having better average immunization coverage in Kyber Pakhtunkhwa, the relative change of 128% in concentration index (CI) from C2 (standard CI) to C5 (when poorer quantile received highest weights) shows this to be also the most inequitable regions. Four parameters of inequality aversion (v = 2, 3, 4 & 5) demonstrated that 'dis - achievement' in completed immunization is densely concentrated among the poorer regions. Balochistan, Sindh and Gilgit Baltistan exhibited broader inequality gaps (93.75%, 83.35%, and 54.93%, respectively) at higher aversion parameter. Conclusions As hypothesized, achievement index uncovers 'penalized' immunization coverage amongst the poorest population. Thus any policy that stringently focuses on improving average immunization rate without any strategy to deal with inequality will only improve immunization rate within wealthier groups. Based on these results, it is advisable to public health policy makers to use both aspect of information: average and degree of inequality in immunization coverage.